Association of objective and subjective socioeconomic markers with cognitive impairment among older adults: cross-sectional evidence from a developing country - Shobhit Srivastava; T Muhammad; TV Sekher (BMJ Open)
Objective This study explored how various markers of objective and subjective socioeconomic status (SES) are associated with cognitive impairment among older Indian adults.Design A cross-sectional study was conducted using large nationally representative survey data.Setting and participant This study used data from the Longitudinal Ageing Study in India (2017–2018). The sample included 31 464 older adults aged 60 years and above.Primary and secondary outcome measures Outcome variable was cognitive impairment, measured through broad domains of memory, orientation, arithmetic function, and visuo-spatial and constructive skills. We estimated descriptive statistics and presented cross-tabulations of the outcome. Χ2 test was used to evaluate the significance level of differences in cognitive impairment by subjective (ladder) and objective SES measures (monthly per-capita consumption expenditure (MPCE) quintile, education and caste status). Multivariable linear and logistic regression analyses were conducted to fulfil the objectives.Results A proportion of 41.7% and 43.4% of older adults belonged to low subjective (ladder) and objective (MPCE) SES, respectively. Older adults with low subjective (adjusted OR (aOR): 2.04; p<0.05) and objective SES (aOR: 1.32; p<0.05) had higher odds of having cognitive impairment in comparison with their counterparts, with a stronger subjective SES–cognitive impairment association. Older adults with lower education or belonged to lower caste had higher odds of cognitive impairment than their counterparts. Interaction analyses revealed that older adults who belonged to lower subjective and objective (poorest MPCE quintile, Scheduled Castes and lowest education) SES had 2.45 (CI: 1.77 to 3.39), 4.56 (CI: 2.97 to 6.98) and 54.41 (CI: 7.61 to 388.93) higher odds of cognitive impairment than those from higher subjective and objective SES, respectively.Conclusion Subjective measures of SES were linked to cognitive outcomes, even more strongly than objective measures of SES; considering the relative ease of obtaining such measures, subjective SES measures are a promising target for future study on socioeconomic indicators of cognitive impairment.